Multiple parasitic infestation in a nine-month-old patient: a case report - Intra J.; Sarto C.; Manuli E.; Vannini P. M.; Brambilla P. (Helminthologia, 2019)
We are reporting the case of a nine-month-old Pakistani female with complaint of growth retardation who presented multiple intestinal parasitic infections. Probably because of contamination with fecal matter, the initial microscopic examination of the urinary sample revealed the presence of eggs of Enterobius vermicularis, cysts of Entamoeba coli, and an organism similar to mites. Stool samples were obtained after two weeks and microscopic investigation confirmed the presence of Enterobius vermicularis eggs, cysts of Entamoeba coli, and hookworm eggs. The patient was immediately subjected to mebendazole therapy associated with trimethoprim-sulfamethoxazole, to which she responded well. Follow-up stool re-examinations performed 15 and 30 days after the treatment tested negative for all parasitic ova and cysts. This study reflects the importance of considering multiple parasitic infestations in low socio-economic populations and highlights the need of improving poor hygienic conditions to prevent such infections, in particular in children.